EP.TU.1069Improved Perioperative and Survival Outcomes for Minimally Invasive Rectal Surgery. (28th October 2021) - Nnaji, Martin; Khan, Kashuf; Hughes, Sam; Inani, Mohit; Yassin, Nuha A
Abstract: Aim: Although laparoscopic colon cancer surgery has been widely embraced as current evidence demonstrates comparable oncological results with open surgery, similar evidence is lacking for laparoscopic rectal cancer surgery. We present the outcomes of patients undergoing laparoscopic and open total mesorectal excision (TME) for rectal cancer in our unit. Methods: We retrospectively analysed data collected for patients who underwent laparoscopic and open TME from January 2014 to December 2018. Sociodemographic, perioperative, circumferential resection margin (CRM) positivity, locoregional recurrence and survival data were analysed. Results: 260 (144 laparoscopic and 116 open) were included. Median age in the laparoscopic group was 69 years and in the open group 68 years. Neoadjuvant therapy was given in 21 patients (14.6%) in laparoscopic and 13 (11.2%) in the open group (p = 0.42). CRM was positive in 16 cases (11.1%) laparoscopic and 32 (27.6%) open (p = 0.0007;95%CI:6.9-26.2). No statistically significant difference in anastomotic leak rate was observed both groups (4.9% laparoscopic vs 4.3% open;p=0.82). Surgical site infection was significantly more in open cases (13% vs 5.6% laparoscopic, p=0.04). Similar locoregional recurrence rates were observed in both groups (18% laparoscopic vs 19% open, p=0.84). Median follow up was 34 months or more allowed for Disease-free (DFS) and overall survival (OS) to be analysed for 144 of 260 patients. DFS and OS were better in laparoscopic (73% and 94%) compared to open (68% and 85% respectively) (p = 0.40 and p = 0.015 respectively). Conclusion: From an oncological perspective, laparoscopic surgery for rectal cancer is safe with additional perioperative and survival benefits compared to open surgery.